Rectangular double-tube concrete columns with an internal elliptical high-strength steel tube: Concept and behavior. (1st August 2020) - Ye, Yu-Yi; Zhu, De-Hua; Zeng, Jun-Jie; Lin, Guan; Wang, Wei-Qiang
Highlights: A pilot study on rectangular double-tube concrete columns (DTCCs) is presented. The post-yield strength of the high strength steel can be effectively utilized in rectangular DTCCs. The axial load-axial strain curves of rectangular DTCCs feature approximately bilinear behavior. The inner steel tube offers additional lateral confinement to core concrete so that the majority of the concrete in a DTCC is effectively confined by the steel tube and the FRP tube. The predicted ultimate axial stresses and strains based on a theoretical model are in agreement with the experimental results. Abstract: This paper presents a novel form of rectangular fiber-reinforced polymer (FRP)-concrete-high strength steel (HSS) hybrid columns referred to as rectangular double-tube concrete columns (DTCCs). These columns consist of a rectangular FRP tube filled with concrete and an elliptical HSS tube as internal reinforcement. The inner elliptical steel tube encloses most of the concrete in the rectangular section and therefore most of the concrete in the section is effectively confined. The high susceptibility of the HSS elliptical tube to local buckling is expected to be suppressed by the confined concrete, leading to full utilization of the high strength of HSS. This paper demonstrates the excellent performance of the new columns due to the above beneficial interactions between different components in the column through an experimental study. In the experimental study, twelve rectangular DTCCs covering different FRP tube thicknesses and aspect ratios were tested under axial compression. Finally, an existing stress–strain model for FRP-confined concrete in rectangular columns is modified to be applicable to the concrete in the new column by accounting for the confinement effect from the inner elliptical HSS tube. It is found that the modified model provides more accurate predictions on the stress–strain curves of confined concrete in the rectangular DTCCs than the original model.